Development of Electrometallic Equipment and Newest Consumables for Applying Protective and Reductive Coatings to Parts of Machinery Used in Mining, Transport, and Food Processing Industries - Student, M.M.; Hvozdetskyi, V.M.; Stupnytskyi, T.R.; Dzioba, Yu.V. (Science and Innovation, 2024)
Design documentation has been developed and pilot industrial prototypes of stationary and manual arc spray gun have been manufactured. The manufactured equipment is intended for spraying protective and reductive coatings by the electric arc metallization method. The manufactured arc spray gun has been provided with power sources, commuting cables, and with control panels designed and manufactured by the author team. The arc spray gun enables to apply antifriction, friction, wear-resistant, corrosionresistant and some other types of coatings from various electrode materials — solid and cored wires. «Gazotermik» small state-owned corporation as partner of R&D project has tested the manufactured arc spray gun equipment and determined the efficiency of developed and optimized cored wires. Cylinder shafts for mining and food processing machinery have been coated using the developed equipment and new electrode materials.